A Confirmatory Factor Analysis Model of Learning Organization, Job Satisfaction, and Work Engagement in the Construction Industry in Bangkok - Preechathammawong, Thanapat; Ramanust, Sumalee (Rajapark Journal, 2026)
This study aimed to examine the levels of learning organization, job satisfaction, and work engagement, and assess the empirical fit of a confirmatory factor analysis (CFA) model. A quantitative research design was employed. The sample consisted of 220 construction workers in Bangkok. The sample size was determined following the guidelines of Hair et al. (2019), using 10-20 observations per parameter. Convenience sampling (a non-probability method) was applied, which may limit the generalizability of the findings. The research instrument was a questionnaire with item–objective congruence (IOC) values ranging from 0.67 to 1.00 and a reliability coefficient of 0.85. Data were analyzed using descriptive statistics (mean and standard deviation) and inferential statistics via CFA with AMOS. The results indicated that the overall levels of the variables were high: Learning Organization ( = 4.00, SD = 0.49), Job Satisfaction ( = 3.96, SD = 0.58), and Work Engagement ( = 3.97, SD = 0.56). The CFA model demonstrated an excellent fit to the empirical data (CMIN/DF = 1.167, CFI = 0.990, TLI = 0.984, RMSEA = 0.029). Factor loadings ranged from 0.59 to 0.87. The composite reliability (CR) was 0.90, and the average variance extracted (AVE) was 0.54, indicating acceptable reliability and convergent validity. Overall, the model exhibited satisfactory construct validity, and the latent variables were positively associated with one another.